2022
DOI: 10.3389/fphys.2022.864547
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Driven Pathogenesis of Atrial Fibrillation in Hypertrophic Cardiomyopathy: The Case of Different TNNT2 Mutations

Abstract: Atrial dilation and atrial fibrillation (AF) are common in Hypertrophic CardioMyopathy (HCM) patients and associated with a worsening of prognosis. The pathogenesis of atrial myopathy in HCM remains poorly investigated and no specific association with genotype has been identified. By re-analysis of our cohort of thin-filament HCM patients (Coppini et al. 2014) AF was identified in 10% of patients with sporadic mutations in the cardiac Troponin T gene (TNNT2), while AF occurrence was much higher (25–75%) in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…5H and Table 1 ), which is expected to disrupt TnT1 interaction with actin rather than with Tm (Fig. 5F ), does not change the affinity of TnT 70-170 fragment to Tm while conferring increased Ca 2+ sensitivity ( 54 ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…5H and Table 1 ), which is expected to disrupt TnT1 interaction with actin rather than with Tm (Fig. 5F ), does not change the affinity of TnT 70-170 fragment to Tm while conferring increased Ca 2+ sensitivity ( 54 ).…”
Section: Discussionmentioning
confidence: 96%
“…Not surprisingly, the TnT1 region is a major hotspot for cardiomyopathy causing mutations ( 52 ) with a high incidence of sudden cardiac death ( 53 ) and atrial fibrillation ( 54 ). Due to the absence of a high-resolution structure of the junction region of the cTF, the underlying molecular mechanisms of these mutations were unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a subsequent study by Lee et al ( 13 ) further demonstrated that HCM patients with likely pathogenic or pathogenic MYH7 variants had a higher risk of incident AF than other sarcomeric genes (MYBPC3, thin filament genes). In addition, patients with sarcomeric gene (e.g., MYH7, TNNT2) variants in hot spot sites that are more frequently associated with HCM development may have higher AF vulnerability in the future than those with gene variants in non-hot spot sites ( 13 , 15 ).…”
Section: Prevalence and Incidence Of Af In Inherited Hcm Patientsmentioning
confidence: 99%
“…Furthermore, the SGCG gene is thought to be linked to AF in a large genome-wide association study ( 24 ). In addition, prior clinical and genetic studies indicated that pathogenic variants in other sarcomere protein genes, including TNNT2, TNNI3, TPM1, MYL2, MYL3 and ACTC1, were associated with the occurrence of ventricular and atrial arrhythmias (particularly AF) ( 15 , 23 ).…”
Section: Cardiomyopathy Gene Variants and Early-onset Afmentioning
confidence: 99%